TRANSFORMATIONAL LEADERSHIP INCREASE SELF FFICACY ON SCHIZOPHRENIC PATIENTS ; A SYSTEMATIC LITERATURE REVIEW - Ashri Maulida Rahmawati; Ifa Nailatul Iza; Zunia Khairunnisa; Budi Istriawan (JURNAL MEDIKA INDONESIA, 2024)
Patients with schizophrenia must have good self-efficacy to recover from their illness. Based on previous research, 47% of patients were still at a low level of self-efficacy. Transformational leadership is leadership that allows the leader to move followers to achieve goals directly. This writing aims to describe the influence of transformational leadership by nurses on self-efficacy for recovery in schizophrenia patients. The method of this writing is a systematic literature review. Literature sources research articles and journals with the keywords "self efficacy", "transformational leadership", and "schizophrenia". The research results showed that four dimensions of transformational leadership can be applied by nurses in increasing the self-efficacy of schizophrenia patients, intellectual stimulation influences mastery experience, ideal influences vicarious experience, inspirational motivation influences verbal persuasion, and individualized attention influences physiological and emotional state. The conclusion of this research is that transformational leadership is suitable for use by nurses in increasing the self-efficacy of schizophrenia patients